Mining Business Licenses for Universities: Legal Barriers Under Indonesian Positive Law - Kurdi; Ibnu Mazjah, R. Muhamad (Jurnal Cakrawala Hukum, 2025)
This article examines the legal compatibility of granting Mining Business Licenses (Izin Usaha Pertambangan, IUP) directly to universities under Indonesian positive law. Using a normative juridical method with statute and conceptual approaches, the article analyses four intersecting regulatory regimes: the Mineral and Coal Mining Law, the Higher Education Law, the State Finance Law, and the Environmental Protection and Management Law. The study finds that universities are not a permissible legal subject to hold IUP under the current mining regime, a position explicitly confirmed by the 2025 amendment to the Mineral and Coal Mining Law, which removed universities from priority access to mining permits. Beyond this statutory exclusion, the proposed policy generates structural incompatibilities with higher-education law, which mandates a non-profit academic mission protected by academic freedom and institutional autonomy; with state finance law, which imposes strict public accountability obligations on university budgets; and with environmental law, which assigns full strict liability for mining damage to the licence holder. The cumulative effect is a normative configuration that Indonesian positive law does not accommodate. The article recommends that university involvement in the mining sector be channelled exclusively through research partnerships, capacity-building agreements, and consultancy arrangements that preserve academic independence and respect the Tri Dharma mandate.